PEMBERDAYAAN GURU DI MADRASAH IBTIDAIYAH (MI) AL-IFADAH PENJARINGAN JAKARTA UTARA - Fatimah, Fatimah; As'ad, As'ad (Universitas Indraprasta PGRI, 2017)
AbstractThe objective of this research was to understand comprehensively the empowerment of teachers’ at the Al-Ifadah Islamic secondary school it was a qualitative research with study case method conducted in Penjaringan, north Jakarta. In this research data collecting with triangulation technique to get credibility in this research grouped as (1) give longer time in research location (2) observation 60 documentation. After with the data categorized and coding were done in two data summary appropriately with the research problem and sub problems then and data analysis about completeness and relevance data examined. The finding lead to the recommendation teacher’s for continues them studies to get more education to apply teachers’ training in term of teacher’s empowerment. Socialization leading and socialization training in order to get the Al-Ifadah Islamic secondary school running well, it is recommended for education head masters and teachers to improve accountability in assessing standard of Islamic secondary school.Key word: teachers’ empowerment, education, training.